DINAMIKA DAN PERKEMBANGAN KONSTITUSI REPUBLIK INDONESIA - Riski Febria Nurita (University of Merdeka Malang, 2017)
Formation of the Indonesian constitution is full of struggle starting from the design process to legalization,done by BPUPKI (Committee for Preparatory Work for Indonesian Independence) or called by DokuritsuZyunbi Tyoosakai, investigators Agency was then formed Basic law, which is planned to cater for independentIndonesia. Basic Law BPUPKI it works by trial PPKI (Committee for Indonesian Independence) August181945 serve as the draft text of the Constitution of the Republic of Indonesia and eventually passed by PPKIandAct of 1945 that eventually became the constitution in our country. Indonesia has been a change in theConstitutionas much as four times include: 1). Act of 194 5; 2). The Constitution RIS (Republic of Indonesia)in1949; 3). While the Constitution of 1950; 4). With the issuance of Presidential Decree dated July 5, 1959,theconstitution in Indonesia back in the Constitution of 1945. Ahead of the 1999 elections, increasing theintensityof political conflict. The condition continues until the implementation of the first amendment to the1945Constitution of the MPR general session 1 until October 20, 1999. Thus, in this situation the firstamendmentof 1945 Constitution in progress, and proceed with the second amendment to the fourth startingfrom1999 until by 2002 with all the problems encountered in these moments.